Photoprotection and skin irritation effect of hydrogels containing hydroalcoholic extract of red propolis: A natural pathway against skin cancer. Issue 2 (February 2022) - Batista, Cinthia M.; de Queiroz, Luma A.; Alves, Ângela V.F.; Reis, Elisiane C.A.; Santos, Fagne A.; Castro, Tailaine N.; Lima, Bruno S.; Araújo, Adriano N.S.; Godoy, Charles A.P.; Severino, Patricia; Cano, Amanda; Santini, Antonello; et al.
Abstract: The use of natural products in sunscreen formulations as a prophylactic measure against skin cancer is receiving special attention attributed to the photoprotective and antioxidant properties of their chemical components. In this work, we describe the development of topical hydrogel formulations containing hydroalcoholic extract of red propolis (HERP), and the evaluation of the dermal sensitizing effect of the developed products. Sunscreen formulations composed of HERP in different concentrations (1.5, 2.5 or 3.5% w/w) alone or in combination with a chemical (octyl methoxycinnamate) and/or physical (titanium dioxide) filters were developed using poloxamer 407 as gel basis. The preliminary and accelerated stability tests, texture analysis and spreadability tests were performed. All formulations revealed to be stable in preliminary stability assessment. The formulations containing HERP 1.5 and 2.5% alone or associated with the filters showed intense modifications during accelerated stability test, which were confirmed by rheological analyses. The incorporation of HERP and filters in the poloxamer hydrogel decreased the toughness of product (p < 0.05) and the formulation containing HERP alone presented the lowest adhesivity (p < 0.001). The incorporation of HERP in the hydrogel decreased the poloxamer transition temperature, showing different rheological behavior with the increase of HERP concentration. The developed formulations were stable, exhibited non-Newtonian and pseudoplastic behavior, showing in vivo skin compatibility and no skin irritancy. Abstract : Red propolis; Photoprotection; Hydrogels; Poloxamer; Sunscreen.